PENGARUH PENDAPATAN TERHADAP PERTUMBUHAN EKONOMI DENGAN BELANJA SEBAGAI MEDIATOR Studi pada Pemerintahan Kabupaten/Kota di Provinsi Jambi - Hermansyah, Hermansyah (Jurnal Khazanah Intelektual, 2024)
The main objective of this study was to determine the indirect effects of local income on economic growth with local expenditure as a mediator variable. In more detail, the objectives of this study are to determine the effect of local income on economic growth with local expenditure as a mediator. The study are is Jambi Province with 11 regencies/cities as the unit of analysis, covering the period 2017-2022. The analytical tool used is path analysis. Local income in this study is translated into four variables, local taxes, provincial tax revenue sharing funds, central tax revenue sharing funds, and general allocation funds. Meanwhile, local expenditure is translated into two variables, personnel expenditure and goods/services and capital expenditure. This study did non find local revenue variables that had an indirect impact on economic growth.